Evaluation of Thyroid Function in Persons having Nodular Goiter without Thyroid Related Symptoms - Shah, Md Kabiruzzaman; Begum, Nasrin; Hossain, Mosharruf; Ahmed, Parvez; Islam, Monoarul; Chowdhuary, Shariful Islam; Ahsan, Mostofa Shamim (Bangladesh Journal of Nuclear Medicine, 2018)
Objective: Objective of this study was to evaluate thyroid hormone level in nodular goiter patient without thyroid related symptoms and normal individual among the population of north-west part along the belt of river Padma. Patients and methods: It was a cross sectional study during the period of one year between July 2005 to June 2006. Total 200 samples were taken within 15 to 50 years age who attended in Institute of Nuclear Medicine & Allied Sciences (INMAS) Rajshahi and OPD Rajshahi Medical college Hospital (RMCH). Diagnosed cases of hypothyroidism, hyperthyroidism, patients treated with radioiodine, pregnant and lactating lady, chronic illness, chronic kidney disease and known cardiac patients were not included in this study. An informed written consent was taken after counseling. Data were collected in predesigned data collection sheet and statistical analysis was performed. Results: Total 100 patients of nodular goiter and 100 normal individual were enrolled for this study. About 37% of study groups were between the age of 20-30 years and 31% in between 30-40 years of age. Male female ratio was 1:2.6. Cold nodular goiter was 75 %, multinodular goiter in 16% cases and partially cold nodular goiter in 9%. The mean ± SD of serum T 3 was 1.89± 0.61 nmol/L and 1.88+-0.44 nmol/L in study and control groups respectively. The mean ± SD of serum T4 was 99.90 ± 29.03 nmol/L and 122.93 ±25.31nmol/L in study and control group and serum TSH was 1.42 ± 1.07 mIU/L and 1.34 ±- 0.54mIU/L in study and control group respectively. Conclusion: This study gave an impression in hormone status of nodular goiter patients in comparison to normal individual. Statistically no significance difference was seen in mean T3 and TSH value between study and control groups however significant difference was seen in mean serum T4 value (p< 0.01). Bangladesh J. Nuclear Med. 19(1): 24-27, January 2016